Алгоритм оцінки і контролю параметрів якості обслуговування в мультисервісній мережі IP/MPLS - Климаш, М.М.; Лаврів, О.А.; Добуш, Ю.Д. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2009)
At present, monitoring of service quality parameters presents an important task for information networks engineering and operation. The key technology for new generation networks is based on package transportation technology IP/MPLS and program commutators Softswitch. Proposed is a checking algorithm for network quality service parameters based on the efficiency of data link layer protocol.